Razvoj socialne varnosti in varovanje človekovega dostojanstva v odločitvah Ustavnega sodišča Republike Slovenije - Korpič-Horvat, Etelka (Podjetje in delo, 2018)
In the intoduction to this article, the author mentions that the future development of society depends on three fundamental factors: economs, social security, and protection of a healthy living environment and nature conservation. These refer to the develompment of economic (material), social, and environmental prosperity. The paper discusses the development of social security and protection of human dignity in the Republic of Slovenia as an important segment of the development of social prosperity and social state. The author presents a number of selected Constitutional Court decisions on the topics of social security rights. The author provides a critical review of those decisons that, in her opinion, have not contributed to the development of a social state. The author establishes that the Constitutional Court adopted a majority of cases in social security matters in the field of pension insurance, a consequence of the fact that almost 30 percent of the Slovene population is retired. The Constitution auhtorises the legislature to regulate the social securist insurances underlying the social security of the population. For these reasons, the Constitutional Court must be reserved when reviewing such insurances. This however, does not signify that the Constitutional Court does not keep watch over the core of such rights. If the legislature interferes with the essence of a human right, as is determined on a case-by-case basis, it also interferes with the right to human dignity. Human dignity, however, is a fundamental value that inherently belongs to every human being.
Keywords: človekova pravica; dostojanstvo; družba blaginje; načelo; socialna država; socialna varnost; ustavno sodišče